2019
DOI: 10.1074/jbc.ra119.011173
|View full text |Cite
|
Sign up to set email alerts
|

Changes in protein function underlie the disease spectrum in patients with CHIP mutations

Abstract: Monogenetic disorders that cause cerebellar ataxia are characterized by defects in gait and atrophy of the cerebellum; however, patients often suffer from a spectrum of disease, complicating treatment options. Spinocerebellar ataxia autosomal recessive 16 (SCAR16) is caused by coding mutations in STUB1, a gene that encodes the multifunctional enzyme CHIP (C terminus of HSC70-interacting protein). The disease spectrum of SCAR16 includes a varying age of disease onset, cognitive dysfunction, increased tendon ref… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…This provides a disease model with endogenous protein levels and the patient's own genetic background. Although mutations in STUB1_1 and STUB1_3 do not alter STUB1 transcript levels, protein stability is strongly reduced by the mutations, leading to a lower CHIP level ( Heimdal et al, 2014 ; Ronnebaum et al, 2014 ; Pakdaman et al, 2017 ; Kanack et al, 2018 ; Shi et al, 2018 ; Madrigal et al, 2019 ). STUB1_2 shows reduced transcript and protein levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This provides a disease model with endogenous protein levels and the patient's own genetic background. Although mutations in STUB1_1 and STUB1_3 do not alter STUB1 transcript levels, protein stability is strongly reduced by the mutations, leading to a lower CHIP level ( Heimdal et al, 2014 ; Ronnebaum et al, 2014 ; Pakdaman et al, 2017 ; Kanack et al, 2018 ; Shi et al, 2018 ; Madrigal et al, 2019 ). STUB1_2 shows reduced transcript and protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…reduced by the mutations, leading to a lower CHIP level (Heimdal et al, 2014;Ronnebaum et al, 2014;Pakdaman et al, 2017;Kanack et al, 2018;Shi et al, 2018;Madrigal et al, 2019). STUB1_2 shows reduced transcript and protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…27 The U-box domain is especially important, as mutations in this domain have a stronger effect on the overall loss of CHIP function and strongly associate with cognitive dysfunction. 28 Indeed, most frameshift mutations identified so far in SCA48 are located in the U-box domain (table e-1, links.lww.com/NXG/A251). 9,11 Whether this results in nonsense mediated RNA decay or a truncated protein (with a possible dominant negative effect) remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies regarding the function of mutated CHIP have reported that some STUB1 mutations mediate disease by affecting the CHIP E3 ubiquitin ligase interactions and function through modification of its oligomeric states and structural stability, which indicates that change in structure may lead to gain-or loss-of-function and thus cause disease. However, we should also note that numerous mutations have limited effects on the structure and ubiquitination activity of CHIP, suggesting that these mutations may affect CHIP function though other mechanisms [13][14][15]118 . The most intensively studied mutation site in vitro and in vivo was T246M, and these studies could serve as grounds for further research of other CHIP mutation sites.…”
Section: Neurological Diseases Caused By Chip Mutationsmentioning
confidence: 99%
“…However, it remains unclear whether there is a relationship between the location of the mutation and changes in the biological function of the corresponding mutated protein with the clinical spectrum of SCAR16. Madrigal et al reported that the mutations located in the U-box domain strongly induce loss of CHIP function and are intensely related to cognitive impairment in patients with SCAR16 118 ; TPR and CC mutations mildly affect CHIP function and are associated with an increased tendon reflex. They also reported that inhibiting the interaction between mutant CHIP and HSP70 can lead to later age of onset and less severe ataxia 118 .…”
Section: Neurological Diseases Caused By Chip Mutationsmentioning
confidence: 99%